Faktor-Faktor Yang Mempengaruhi Produksi Salak Mangguang Menggunakan Analisis Regresi Linear Berganda - Wahyuni, Putri; Winanda, Rara Sandhy (Journal of Mathematics UNP, 2024)
The center of snake fruit mangguang recency is in Kenagarian Tanjung Beringin. Mangguang salak production fluctuates every year. From 2019-2022, snake fruit production has decreased, which has an impact on the economy of the people in the area. The aim of this research is to identify factors that have a significant influence on the production of Mangguang salak in Pasaman Regency. The analysis used is multiple linear regression analysis. From the research results, the factors that most significantly influence the production of mangguang salak are the number of clumps and pruning with an error rate of 5%.